Graded multilayer water-resistant low-temperature rare earth-based denitration catalytic fiber material as well as preparation method and application thereof

By using the graded multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material with Ce-UiO-66 and ZIF-8 as active components, the existing low-temperature denitrification catalysts are solved inadequate catalytic activity under complex flue gas conditions in the non-electric industry, and the efficient, stable and low-cost flue gas denitrification effect is achieved.

CN119565675AActive Publication Date: 2025-03-07NANJING TECH UNIV +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411505621.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing low-temperature denitrification catalysts are insufficient in complex flue gas conditions in the non-electric industry, and the preparation raw materials are complicated and costly, making it difficult to adapt to large-scale industrial applications.

Method used

The polyacrylonitrile PAN fiber is used as the support, and the material formed by Ce-UiO-66 and ZIF-8 is used as the active component. The graded multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material is prepared through pentafluorobenzene modification.

Benefits of technology

The catalyst has a denitrification efficiency of more than 80% in the temperature range of 90-180°C. It has good water and dust resistance, strong stability, low cost, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565675A_ABST
    Figure CN119565675A_ABST
Patent Text Reader

Abstract

The invention discloses a graded multilayer water-resistant low-temperature rare-earth-based denitration catalytic fiber material and a preparation method and application thereof, the catalytic fiber material takes PAN fiber as a carrier and an MOF / MOF material formed by Ce-UiO-66 and ZIF-8 as an active component, and the surface of the active component is modified by pentafluorobenzene. According to the method, graded multi-layer synthesis of active components is controlled by adopting a special pore channel chip, pentafluorobenzene is taken as a surface modifier and an acid site enhancer, and the Ce-UiO-66 / ZIF-8-coated PAN catalytic fiber material is synthesized in one step by combining micro-fluidic electrostatic spinning with reaction self-heating. The catalyst synthesized by the method has a hierarchical multilayer MOF / MOF structure, is high in hydrophobicity and large in specific surface area, and can efficiently and stably realize the denitration target under the low-temperature flue gas working condition in the non-electric industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graded multi-layer water-resistant low-temperature rare earth-based denitration catalytic fiber material, belonging to the field of industrial flue gas purification in non-electricity industries. Background Art

[0003] As the most commonly used NO x The removal method NH3-SCR method is the technical core, and the research and development of new denitrification catalysts is urgent. At present, the commercial catalysts for fixed source flue gas denitrification mainly include vanadium-based catalysts and rare earth-based catalysts. However, commercial vanadium-based catalysts still have some inevitable defects, such as poor low-temperature activity, volatility and biological toxicity of V2O5, which seriously hinder their further development in practical applications. Denitrification catalysts with rare earth elements such as Ce as active components can not only effectively reduce NO x It can also prevent the pollution of the atmosphere and secondary pollution of the environment by toxic element V, but rare earth-based catalysts still face problems such as insufficient activity under low temperature conditions.

[0004] Among the existing low-temperature denitration patents, patent CN202110032477.8 mixes the molecular sieve acid catalyst with the transition metal oxide in a grinding manner, and mechanically grinds the redox catalyst and the acid catalyst to fully contact each other, which can effectively increase the acidity of the redox catalyst, and at the same time will not affect the redox performance of the catalyst itself due to chemical reactions, so that the catalyst has strong resistance to ammonium nitrate poisoning under low temperature conditions. Patent CN202011527738.5 discloses a low-temperature denitration catalyst and a preparation method thereof, the low-temperature denitration catalyst includes a cordierite carrier and an active component coated on the carrier, the active components are mainly V2O5, MoO3, SiO2, TiO2 and phosphate ions, and the resulting catalyst has good low-temperature catalytic activity and sulfur resistance. Patent CN202011289497.5 discloses a method for preparing a low-temperature denitration catalyst from manganese ore. The method uses manganese ore as the main raw material to prepare a low-temperature denitration catalyst, including crushing, grinding, component blending, mixing, molding, drying, and roasting steps, which realizes the high-value utilization of manganese ore and reduces the production cost of the low-temperature denitration catalyst. Although the above-mentioned catalyst has achieved a certain degree of efficient low-temperature denitration activity, some of them use V or precious metals as the only active component, resulting in expensive catalyst costs and unsuitable for large-scale industrial applications. The other part has complicated raw materials for preparation, is difficult to prepare, and is insufficient in its ability to resist SO2 and water vapor under complex flue gas conditions in non-electricity industries. Summary of the invention

[0005] The purpose of the present invention is to address the problem of insufficient catalytic activity of low-temperature denitration catalysts caused by the existing flue gas conditions in non-electric industries where flue gas contains low levels of pollutants such as water and sulfur, and to propose a preparation method and application of a graded, multi-layer, water-resistant, low-temperature rare earth-based denitration catalytic fiber material.

[0006] A hierarchical multilayer water-resistant low-temperature rare earth-based denitrification catalytic fiber material, the catalytic fiber material uses polyacrylonitrile (PAN) fiber as a carrier, a material formed by Ce-UiO-66 and ZIF-8 as an active component, and the surface of the active component is modified with pentafluorobenzene; wherein the mass percentage of the active component is 1-15% based on the mass of the carrier.

[0007] In some preferred technical solutions: based on the mass of the carrier, the mass percentage of the active component is 2-8%.

[0008] In the above-mentioned graded multilayer water-resistant low-temperature rare earth-based denitrification catalytic fiber material: the mass ratio of Ce-UiO-66 to ZIF-8 is 1: (1-15), and the mass ratio of pentafluorobenzene to the active component is 1: (10-60).

[0009] In some preferred technical solutions: the mass ratio of Ce-UiO-66 to ZIF-8 is 1:(5-10), and the mass ratio of pentafluorobenzene to the active component is 1:(20-40).

[0010] A method for preparing the above-mentioned catalytic fiber material, the method for preparing the catalytic fiber material is as follows:

[0011] (1) Preparation of PAN carrier spinning solution

[0012] Dissolve PAN in solvent 1 and stir evenly to obtain PAN spinning solution A;

[0013] (2) Preparation of active component precursor solution

[0014] The zinc source and 2-methylimidazole are dissolved in solvent 1 and stirred to obtain solution B; the cerium salt, formic acid and terephthalic acid are dissolved in solvent 1 and stirred to obtain Ce-UiO-66 precursor solution C; pentafluorobenzene is dissolved in solvent 1 and stirred to obtain solution D;

[0015] (3) Preparation of catalytic fiber materials

[0016] Solutions A, B, C, and D are injected into the microchannels of the microfluidic control chip through multiple sets of micro-injection pumps, mixed evenly to obtain the spinning stock solution, and finally electrospun by a microfluidic electrospinning machine. After the fiber forming is completed, it is dried at room temperature to obtain a graded multi-layer water-resistant, low-temperature rare earth-based denitrification catalytic fiber material.

[0017] In the above preparation method: the molecular weight of PAN described in step (1) is 100000-150000; the mass ratio of PAN to solvent 1 in the solution A is 1:(10-12.5); and the solvent 1 is N,N-dimethylformamide.

[0018] In the above preparation method: the zinc source in step (2) is zinc nitrate hexahydrate, and the mass ratio of the zinc source, 2-methylimidazole and solvent 1 in solution B is 1:(2-7):(15-45);

[0019] The cerium salt described in step (2) is ammonium cerium nitrate hexahydrate, and the mass ratio of the cerium salt, terephthalic acid, formic acid and solvent 1 in solution C is 1: (0.1-0.5): (1-5): (45-105);

[0020] The mass ratio of pentafluorobenzene to solvent 1 in the solution D described in step (2) is 1:(20-100);

[0021] The solvent 1 is N,N-dimethylformamide.

[0022] In the above preparation method: the injection rate of the microinjection pump described in step (3) is 0.1-25 mL / h; the spinning voltage of the electrospinning machine is 15-25 kV.

[0023] In the above preparation method: in step (3), the microchannels of the microfluidic control chip are provided with channels for conveying solution A and solution B, both of which are connected to the main pipe, at least two pipes for conveying solution C are also connected to the main pipe, and the output end of the main pipe is connected to the pipe for conveying solution D, so that the mixed solution composed of the solution at the output end of the main pipe and solution D is the spinning solution;

[0024] Preferably, solution A is injected into the main channel, solution B also enters the main channel and mixes with spinning solution A, and after mixing, solution C also enters the pipeline for reaction. The reaction is an exothermic reaction, and the released heat is transferred to the main channel to guide the synthesis of ZIF-8, so that Ce-UiO-66 is loaded on the surface of ZIF-8 to form a MOF / MOF structure, and then the pentafluorobenzene solution modifies the MOF / MOF active components, and finally a uniformly mixed spinning solution is obtained at the tail end of the chip.

[0025] Most preferably, the injection pump flow rates of solutions A, B, C, and D are set to 10-30 mL / h, 1-10 mL / h, 0.5-2 mL / h, and 0.01-2 mL / h, respectively.

[0026] In the technical solution of the present invention, the catalytic fiber material is used in the denitrification of low-temperature flue gas in non-electric industries, and the non-electric industries are the steel industry, cement industry, non-ferrous metal smelting and chemical industry.

[0027] The experimental conditions for evaluating the activity of the catalyst of the present invention are as follows: 0.1 g of fiber material is poured into a quartz tube with an inner diameter of 6 mm, fixed with quartz wool and wire mesh, and the quartz tube is placed in a tubular furnace, and the actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tubular furnace. Intake gas components: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), and the rest are N2, the total gas flow rate is 100 mL / min, the temperature is controlled at 90-180°C, and it stays stable for 30 minutes every 30°C, and the NO concentration is tested using a Laoying 3021 portable carbon emission monitor. The catalyst denitrification efficiency is higher than 80% in the temperature range of 90-180°C.

[0028] Beneficial effects:

[0029] (1) PAN nanofibers have small diameter, high porosity, large specific surface area, good adsorption performance, and good aging resistance under complex flue gas conditions in non-electricity industries. Since the pore size of the catalytic material formed by the whole is smaller than that of traditional fibers, it can effectively filter micron-sized particles in the flue gas, improving the dust resistance of the catalytic material.

[0030] (2) Ce has an unfilled 4f electron layer structure, forming Ce-UiO-66. 3+ / Ce 4+ coexistence state, accompanied by the generation of oxygen vacancies, Ce 3+ / Ce 4+ The rapid conversion between them brings more free electrons and promotes the adsorption and activation of molecular oxygen, thereby improving the oxygen storage and release capacity and oxidation activity of the catalytic material, and effectively ensuring the redox ability of the catalytic material.

[0031] (3) ZIF-8 has high porosity, large specific surface area and excellent adsorption performance. First, it effectively improves the bonding strength and loading effect between Ce-UiO-66 and its surface. The layered MOF composite structure formed exposes the more catalytically active Ce-UiO-66 in the outer layer and enhances the more adsorbent ZIF-8 in the inner layer, making the catalytic material more effective in adsorbing denitrification reactants such as NO, NH3 and O2, thereby improving the overall catalytic performance. At the same time, ZIF-8 has strong stability and can maintain its structural integrity under conditions such as water and flue gas temperature of 180°C. The loss of active components of the catalyst is small, and the catalyst has strong long-term operation stability.

[0032] (4) The advantages of pentafluorobenzene surface modification are mainly manifested in the following two aspects. First, the increase in the fluorine content on the surface of the MOF material can enhance the hydrophobicity of the material and improve the durability of the catalytic material in an aqueous environment. Second, the electron-rich fluorine atoms on the pentafluorophenyl group can serve as Lewis basic sites, thereby promoting the adsorption of NO onto the catalyst surface and improving the NO removal efficiency of the catalytic material.

[0033] (5) Based on special chip ( Figure 1 ) channel realizes the hierarchical synthesis of catalyst active components and efficient mixing with carrier solution. According to the chip channel sequence, ZIF-8 precursor solution is directly mixed with PAN carrier solution, and the outside of ZIF-8 synthesis channel is Ce-UiO-66 synthesis channel. When Ce-UiO-66 is synthesized, the solution itself will spontaneously and quickly generate heat, providing heating conditions for the synthesis of ZIF-8. This section consumes the excess heat spontaneously generated by the system, and ZIF-8 can be synthesized quickly and efficiently under heating conditions. The synthesized ZIF-8 and Ce-UiO-66 are compounded and injected with pentafluorobenzene solution at the tail, finally forming a spinning stock solution with uniform active component mixing. The surface active components of the catalytic fiber material formed by electrospinning are evenly dispersed and have high bonding strength. The step-by-step synthesis process of active components and fiber carriers is reduced to one-step synthesis, effectively improving the production efficiency of catalytic materials.

[0034] Therefore, the catalyst prepared by the present invention can not only realize the efficient removal of nitrogen oxides in flue gas, but also the catalytic material has strong water and dust resistance and excellent stability under complex flue gas operating conditions in non-electricity industries. Moreover, the catalyst component is environmentally friendly, the preparation process is simple, the cost is low, the cost performance is high, and it has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a schematic diagram of a channel of a chip applicable to the present invention;

[0036] Figure 2 A physical diagram of the chip;

[0037] Figure 3 This is a SEM image of the catalytic material prepared in Example 3;

[0038] Figure 4 This is a graph showing the NO removal performance of the catalytic materials prepared in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following examples.

[0040] Example 1

[0041] (1) Preparation of PAN carrier spinning solution

[0042] 10.0000 g of polyacrylonitrile (molecular weight 150000) was weighed and dissolved in 100.0000 g of N, N-dimethylformamide and stirred at room temperature to obtain PAN spinning solution A, wherein the mass ratio of PAN to DMF was 1:10;

[0043] (2) Preparation of active component precursor solution

[0044] Based on the mass of the carrier, the mass percentage of the active component is 5%, and the mass ratio of Ce-UiO-66 to ZIF-8 in the active component is 1:8. 0.5759 g of zinc nitrate hexahydrate and 2.8793 g of 2-methylimidazole were weighed and dissolved in 11.5172 g of DMF and stirred evenly at room temperature to obtain solution B, wherein the mass ratio of zinc salt, 2-methylimidazole and DMF was 1:5:20; 0.0905 g of cerium ammonium nitrate hexahydrate, 0.0905 g of formic acid and 0.0090 g of terephthalic acid were weighed and dissolved in 4.5236 g of DMF and stirred evenly at room temperature to obtain Ce-UiO-66 precursor solution C, wherein the mass ratio of cerium salt, terephthalic acid, formic acid and DMF was 1:0.1:1:50; 0.0250 g of pentafluorobenzene was weighed and dissolved in 0.5000 g of DMF and stirred evenly at room temperature to obtain solution D, wherein the mass ratio of pentafluorobenzene to active component was 1:20.

[0045] (3) Preparation of catalytic fiber materials

[0046] Based on channel chip ( Figure 1 ), solutions A, B, C, and D are injected into the microchannels of the microfluidic control chip through multiple groups of microinjection pumps, wherein the injection pump flow rates of solutions A, B, C, and D are set to 20.000 mL / h, 2.303 mL / h, 0.905 mL / h, and 0.100 mL / h, respectively, and ZIF-8 synthesis, Ce-UiO-66 synthesis, and pentafluorobenzene modification are carried out in the order of flow, and a uniformly mixed spinning stock solution is obtained at the tail end of the chip, and finally, electrospinning is carried out by a microfluidic electrospinning machine, and the spinning voltage of the electrospinning machine is 25 kV. After the fiber forming is completed, it is dried at room temperature to obtain a graded multilayer water-resistant low-temperature rare earth-based denitrification catalytic fiber material.

[0047] (4) Catalytic activity test

[0048] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ reaches 87.5% at 5min, and the denitrification efficiency at 120-180℃ is 100% at 5min.

[0049] Example 2

[0050] (1) Preparation of PAN carrier spinning solution

[0051] 10.0000 g of polyacrylonitrile (molecular weight 100000) was weighed and dissolved in 125.0000 g of N, N-dimethylformamide and stirred at room temperature to obtain PAN spinning solution A, wherein the mass ratio of PAN to DMF was 1:12.5;

[0052] (2) Preparation of active component precursor solution

[0053] Based on the mass of the carrier, the mass percentage of the active component is 2%, and the mass ratio of Ce-UiO-66 to ZIF-8 in the active component is 1:5. 0.2159 g of zinc nitrate hexahydrate and 0.8638 g of 2-methylimidazole were weighed and dissolved in 8.6379 g of DMF and stirred at room temperature to obtain solution B, wherein the mass ratio of zinc salt, 2-methylimidazole and DMF was 1:4:40; 0.0271 g of cerium ammonium nitrate hexahydrate, 0.0543 g of formic acid and 0.0054 g of terephthalic acid were weighed and dissolved in 2.7141 g of DMF and stirred at room temperature to obtain Ce-UiO-66 precursor solution C, wherein the mass ratio of cerium salt, terephthalic acid, formic acid and DMF was 1:0.2:2:100; 0.0061 g of pentafluorobenzene was weighed and dissolved in 0.6111 g of DMF and stirred at room temperature to obtain solution D, wherein the mass ratio of pentafluorobenzene to active component was 1:30.

[0054] (3) Preparation of catalytic fiber materials

[0055] Based on a specially designed channel chip ( Figure 1), solutions A, B, C, and D are injected into the microchannels of the microfluidic control chip through multiple groups of microinjection pumps, wherein the injection pump flow rates of solutions A, B, C, and D are set to 25.000 mL / h, 1.728 mL / h, 0.543 mL / h, and 0.122 mL / h, respectively, and ZIF-8 synthesis, Ce-UiO-66 synthesis, and pentafluorobenzene modification are carried out in the order of flow, and a uniformly mixed spinning stock solution is obtained at the tail end of the chip, and finally, electrospinning is carried out by a microfluidic electrospinning machine, and the spinning voltage of the electrospinning machine is 15 kV. After the fiber forming is completed, it is dried at room temperature to obtain a graded multilayer water-resistant low-temperature rare earth-based denitrification catalytic fiber material.

[0056] (4) Catalytic activity test

[0057] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ reaches 84.5% at 5min, and the denitrification efficiency at 120-180℃ is 100% at 5min.

[0058] Example 3

[0059] (1) Preparation of PAN carrier spinning solution

[0060] 10.0000 g of polyacrylonitrile (molecular weight 150000) was weighed and dissolved in 100.0000 g of N, N-dimethylformamide and stirred at room temperature to obtain PAN spinning solution A, wherein the mass ratio of PAN to DMF was 1:10;

[0061] (2) Preparation of active component precursor solution

[0062] Based on the mass of the carrier, the mass percentage of the active component is 8%, and the mass ratio of Ce-UiO-66 to ZIF-8 in the active component is 1:10. 0.9423 g of zinc nitrate hexahydrate and 4.7116 g of 2-methylimidazole were weighed and dissolved in 37.6927 g of DMF and stirred evenly at room temperature to obtain solution B, wherein the mass ratio of zinc salt, 2-methylimidazole and DMF was 1:5:40; 0.1184 g of cerium ammonium nitrate hexahydrate, 0.1184 g of formic acid and 0.0118 g of terephthalic acid were weighed and dissolved in 5.9218 g of DMF and stirred evenly at room temperature to obtain Ce-UiO-66 precursor solution C, wherein the mass ratio of cerium salt, terephthalic acid, formic acid and DMF was 1:0.1:1:50; 0.0200 g of pentafluorobenzene was weighed and dissolved in 1.0000 g of DMF and stirred evenly at room temperature to obtain solution D, wherein the mass ratio of pentafluorobenzene to active component was 1:40.

[0063] (3) Preparation of catalytic fiber materials

[0064] Based on a specially designed channel chip ( Figure 1 ), solutions A, B, C, and D are injected into the microchannels of the microfluidic control chip through multiple groups of microinjection pumps, wherein the injection pump flow rates of solutions A, B, C, and D are set to 20.000 mL / h, 7.539 mL / h, 1.184 mL / h, and 0.200 mL / h, respectively, and ZIF-8 synthesis, Ce-UiO-66 synthesis, and pentafluorobenzene modification are carried out in the order of flow, and a uniformly mixed spinning stock solution is obtained at the tail end of the chip, and finally electrospinning is carried out by a microfluidic electrospinning machine, and the spinning voltage of the electrospinning machine is 25 kV. After the fiber forming is completed, it is dried at room temperature to obtain a graded multilayer water-resistant low-temperature rare earth-based denitrification catalytic fiber material.

[0065] (4) Catalytic activity test

[0066] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ reaches 93.4% at 5min, and the denitrification efficiency at 120-180℃ is 100% at 5min.

[0067] Comparative Example 1

[0068] (1) Preparation of active component precursor solution

[0069] Except that Ce-UiO-66 precursor solution is not added to the active component precursor solution, other conditions are the same as those in Example 1;

[0070] (2) Catalytic activity test

[0071] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ reaches 50.7% at 5min, and the denitrification efficiency at 180℃ is 60.3% for 5min.

[0072] (3) Contrast effect

[0073] Compared with Example 1, Ce-UiO-66 precursor solution is not added during the preparation of the active component precursor solution, resulting in a catalytic fiber material in which a single ZIF-8 is loaded on PAN fiber, and the strong redox ability of the active component Ce-UiO-66 is lost, resulting in a significant decrease in NO removal performance.

[0074] Comparative Example 2

[0075] (1) Preparation of catalytic fiber materials

[0076] Except that the carrier and the active component are not formed in one step by microfluidic electrospinning during the preparation of the catalytic fiber material, but are formed in steps and then impregnated and combined, the other conditions are the same as those in Example 2;

[0077] (2) Catalytic activity test

[0078] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ reaches 10.7% at 5min, and the denitrification efficiency at 180℃ is 31.5% for 5min.

[0079] (3) Contrast effect

[0080] Compared with Example 2, when preparing the catalytic fiber material, the carrier and the active components are not formed in a one-step manner by microfluidic electrospinning, but are formed in steps and then impregnated and combined, resulting in low bonding strength between the MOF material and the fiber carrier, poor loading effect, and seriously insufficient content of active components in the fiber material, resulting in a serious decrease in denitrification efficiency.

[0081] Comparative Example 3

[0082] (1) Preparation of active component precursor solution

[0083] Except that the pentafluorobenzene solution is not added to the active component precursor solution, other conditions are the same as those in Example 3;

[0084] (2) Catalytic activity test

[0085] Take 0.1g of catalytic fiber material, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), the rest are N2, the total gas flow rate is 100mL / min, the temperature is controlled at 90-180℃, stay stable for 30min every 30℃, and use Laoying 3021 portable carbon emission monitor to test NO concentration. The denitrification activity of the catalytic fiber material at 90℃ is 54.3% at 5min, and the denitrification efficiency at 180℃ is 68.1% at 5min.

[0086] (3) Contrast effect

[0087] Compared with Example 3, pentafluorobenzene solution was not added during the preparation of the active component precursor solution, the adsorption performance of the catalytic fiber material for reactant molecules decreased, and the water resistance decreased, resulting in a significant decrease in NO removal performance.

Claims

1. A hierarchical multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material, characterized in that: The catalytic fiber material uses polyacrylonitrile PAN fiber as a carrier, a material formed by Ce-UiO-66 and ZIF-8 as an active component, and the surface of the active component is modified with pentafluorobenzene; wherein the mass percentage of the active component is 1-15% based on the mass of the carrier.

2. The hierarchical multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material according to claim 1 is characterized in that: Based on the mass of the carrier, the mass percentage of the active component is 2-8%.

3. The hierarchical multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material according to claim 1 is characterized in that: The mass ratio of Ce-UiO-66 to ZIF-8 is 1:(1-15), and the mass ratio of pentafluorobenzene to active component is 1:(10-60).

4. The hierarchical multi-layer water-resistant low-temperature rare earth-based denitrification catalytic fiber material according to claim 3 is characterized by: The mass ratio of Ce-UiO-66 to ZIF-8 is 1:(5-10), and the mass ratio of pentafluorobenzene to active component is 1:(20-40).

5. A method for preparing the catalytic fiber material according to claim 1, characterized in that: The preparation method of the catalytic fiber material is as follows: (1) Preparation of PAN carrier spinning solution Dissolve PAN in solvent 1 and stir evenly to obtain PAN spinning solution A; (2) Preparation of active component precursor solution The zinc source and 2-methylimidazole are dissolved in solvent 1 and stirred to obtain solution B; the cerium salt, formic acid and terephthalic acid are dissolved in solvent 1 and stirred to obtain Ce-UiO-66 precursor solution C; pentafluorobenzene is dissolved in solvent 1 and stirred to obtain solution D; (3) Preparation of catalytic fiber materials Solutions A, B, C, and D are injected into the microchannels of the microfluidic control chip through multiple sets of micro-injection pumps, mixed evenly to obtain the spinning stock solution, and finally electrospun by a microfluidic electrospinning machine. After the fiber forming is completed, it is dried at room temperature to obtain a graded multi-layer water-resistant, low-temperature rare earth-based denitrification catalytic fiber material.

6. The preparation method according to claim 5, characterized in that: The molecular weight of PAN described in step (1) is 100,000-150,000; the mass ratio of PAN to solvent 1 in the solution A is 1:(10-12.5); and the solvent 1 is N,N-dimethylformamide.

7. The preparation method according to claim 5, characterized in that: The zinc source in step (2) is zinc nitrate hexahydrate, and the mass ratio of the zinc source, 2-methylimidazole and solvent 1 in solution B is 1:(2-7):(15-45); The cerium salt described in step (2) is ammonium cerium nitrate hexahydrate, and the mass ratio of the cerium salt, terephthalic acid, formic acid and solvent 1 in solution C is 1: (0.1-0.5): (1-5): (45-105); The mass ratio of pentafluorobenzene to solvent 1 in the solution D described in step (2) is 1:(20-100); The solvent 1 is N,N-dimethylformamide.

8. The preparation method according to claim 5, characterized in that: The injection rate of the microinjection pump described in step (3) is 0.1-25 mL / h; the spinning voltage of the electrospinning machine is 15-25 kV.

9. The preparation method according to claim 5, characterized in that: In step (3), the microchannels of the microfluidic control chip are provided with channels for conveying solution A and solution B, both of which are connected to the main pipe, at least two pipes for conveying solution C are also connected to the main pipe, and the output end of the main pipe is connected to the pipe for conveying solution D, so that the mixed solution composed of the solution at the output end of the main pipe and solution D is the spinning solution; Preferably: solution A is injected into the main channel, solution B also enters the main channel and mixes with spinning solution A, and after mixing, solution C also enters the pipeline for reaction, which is an exothermic reaction, releasing heat and transferring it to the main channel to guide the synthesis of ZIF-8, so that Ce-UiO-66 is loaded on the surface of ZIF-8 to form a MOF / MOF structure, and then pentafluorobenzene solution modifies the MOF / MOF active components, and finally a uniformly mixed spinning solution is obtained at the tail end of the chip; Most preferably, the injection pump flow rates of solutions A, B, C, and D are set to 10-30 mL / h, 1-10 mL / h, 0.5-2 mL / h, and 0.01-2 mL / h, respectively.

10. Application of the catalytic fiber material of claim 1 in low-temperature flue gas denitrification in non-electricity industries, wherein the non-electricity industries are the steel industry, cement industry, non-ferrous metal smelting and chemical industry.

Citation Information

Patent Citations

  • Method for preparing low-temperature denitration catalyst from manganese ore

    CN112427033A

  • Low-temperature denitration catalyst and application thereof

    CN112619693A

  • A low-temperature denitrification catalyst and its preparation method

    CN112675885B

  • Carbon-coated high-capacity lithium-rich manganese ternary cathode material with MOF as carbon source and preparation method thereof

    CN109742349A

  • SCR low-temperature denitration catalyst based on ZIF-67 porous carbon skeleton modification, and preparation method of SCR low-temperature denitration catalyst

    CN110368991A